Corporate social responsibility and sustainability in the tourism sector: A systematic literature review and future outlook. (2nd November 2021) - Madanaguli, Arun; Srivastava, Shalini; Ferraris, Alberto; Dhir, Amandeep
Abstract: The current study intends to synthesise extant studies addressing corporate social responsibility (CSR) and sustainability in the tourism sector. It employed qualitative content analysis to present the research profile, prominent conceptual, qualitative and quantitative studies, research gaps and future research questions. The review results indicate that research on CSR in tourism is a promising area of study that is growing rapidly. This review captures conceptual, qualitative and quantitative empirical studies and divides them into themes based on two typologies. Typology 1 addresses the direct effect of CSR on employees, customers and business performance. Typology 2 highlights the moderated and mediated relationships of variables, including customer trust, identification, trust and value with CSR. The findings provide a unifying framework highlighting the importance of CSR engagement in building relationships with various stakeholders in the tourism industry context. This contribution is one of the first reviews to examine the growing research on the CSR agenda in tourism. The tourist industry should recognise stakeholders' roles and attempt to involve them in their CSR initiatives.